Promoting the role of the leader in implementing digital transformation in state agencies - Nguyen Thi Hai Van (Journal of State Management, 2024)
Digital transformation is a central strategy aimed at modernizing, enhancing the efficiency of state management, and promoting socio- economic development. The Prime Minister issued Directive No. 34/CT-TTg on September 16, 2024, requiring ministries, sectors, and localities to build digital transformation plans while identifying shortcomings in implementing previous digital transformation programs. This indicates that some leaders still need to regard it as a central task. The Directive also emphasizes the leader's critical role in managing and allocating resources to effectively implement digital transformation and better meet the needs of citizens and businesses. This article analyses several challenges facing leaders in digital transformation and proposes solutions to enhance effectiveness.